Process Developments in Electron-Beam Powder Bed Fusion Enabled by Near-Infrared Radiation - William Sjöström; Lars-Erik Rännar; Carlos Botero; Laia Ortiz Membrado (Journal of Manufacturing and Materials Processing)
The use of an electron beam (EB) as a heating source in EB-based powder bed fusion (PBF-EB) has several limitations, such as reduced powder recyclability, short machine service intervals, difficulties with heating large areas and the limited processability of charge-sensitive powders. Near-infrared (NIR) heating was recently introduced as a feasible replacement and/or complement to EB heating in PBF-EB. This work further investigates the feasibility of using NIR to eliminate the need for a build platform as well as to enable easier repairing of parts in PBF-EB. NIR-assisted Ti-6Al-4V builds were successfully carried out by starting from a loose powder bed without using a build platform. The results do not only confirm that it is possible to eliminate the build platform by the aid of NIR, but also that it can be beneficial for the process cleanliness and improve the surface quality of built parts. Furthermore, a 430 stainless-steel (SS) component could be repaired by positioning it in a loose 316L SS powder bed using a fully NIR-heated PBF-EB process.